Towards a Comprehensive Approach to Clinical Education: A Response to the New Reality - Terence J. Anderson; Robert S. Catz (Washington University Law Quarterly, 1981)
In this Article, we describe one model through which the process could be initiated and the results evaluated within the economic and educational structure of the contemporary university law school.
Keywords: Law school; Legal education; United States